The Effects of Entrepreneurship Learning Methods To Learners Entrepreneurship Interest - Andy Irawan, Herlina (International Journal Pedagogy of Social Studies, 2017)
The results of this research based on the sports data and students have passed entrepreurship whois learning that the interest they did not grow optimally . Found school tuition who have passedin two years to five years had not previously been many of those who seek to have their ownbusinesses . The limitation of synthesis trouble taken is the learning methods in the classroomand outside of class that is set as variable free and interest of entrepreneurship as variable bound.Research methodology used in this research is a method of quantitative research surveyeksplanasi with the approach. Data processing using analysis Pearson Product Poment andDouble Correlations. The purpose of this research is to know how big the influence of thelearning methods both inside and outside of class against interest of entrepreneurship schooltuition. From the results of this study researchers were able to give advice to the teachers field ofstudy marketing and related parties to the students interest of entrepreneurship. The conclusionof this research is the existence of a fairly significant effect of a method of learning in theclassroom and outside of the students interest of entrepreneurship.